(untitled) (Eurasian Medical Research Periodical, 2024)
Numerous anomalies of bowel and fixation are defined as «incomplete bowel rotation» by many authors. In foreign literature, the term "malrotation" is adopted. This review presents current information on embryogenesis and variants of bowel rotation and fixation anomalies, reveals certain differences in manifestations and teratogenesis depending on its anatomical variant, which can be useful in choosing the tactics of surgical treatment in the neonatal period.